PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP STRES KERJA GURU DI SMAN 12 ENREKANG - Sawal Sawal; Muh. Ichwan Musa; Zainal Ruma (CV. ADIBA AISHA AMIRA, 2022)
This research aims to know the effect of workload and work environment on teacher work stress at SMAN 12 Enrekang. The population in this study were all 20 teachers at SMAN 12 Enrekang. Determining the saturated sample or the entire population is sampled. The method data collection was observation, questionnaires, and interviews. The data analysis were reliability, hypothesis testing consisting of multiple linear regression test, t test, f test, and R Square test with using Statistical Product and Service Solution (SPSS version 24). The results of workload variable partially has a relationship with the regression coefficient which has a positive value of 0.587 and has an effect on work stress. This is evidenced by the value of t value (2.794) > t table (1.73961) significant value obtained 0.012 < 0.05. The work environment variable partially affects work stress, which has a negative value of 0.392. This is evidenced the value of t value (2.361) > (1.73961) with a significant obtained (0.030) < (0.05). Simultaneously of two independent variables have a significant effect on work stress. This is evidenced by the value of F value 9.249 > Ftable 3.590 with a significant level of (0.002) < (0.005).